Interpersonal Communication Competency of Researchers Based Personality Typilogy (Kompetensi Komunikasi Interpersonal Peneliti Berdasarkan Tipologi Kepribadian) - Mia Rahma Romadona (BBPSDMP KOMINFO MAKASSAR, 2016)
Communication is one of the competencies that must be owned by the Head of LIPI researcher under Regulation No. 04 of 2009 concerning the standard of competence investigators. The lack of interpersonal communication skills in HR researcher becomes a dilemma for individual researchers and organizations, as it would result in less than the maximum dissemination of information will be the results of research into the environmental and social studies. Jung's personality typology with The Myers-Briggs Type Indicator (MBTI) to describe the interpersonal communication skills, explain the indicator, and interpretation. Measurement of personality typology MBTI researchers used a questionnaire survey research center X purposive random sampling involved 42 researchers covering two reasearch group namely policy and science and technology indicators, and management of science and technology. There are twelve of personality typology balance between introvert and extrovert personality. A description of the competence of interpersonal communication as part of self-concept, related to the appearance of the researcher in communication that can help interpersonal perception of the interlocutor. Indicators that describe the ability of researchers interpersonal competence is the ability to provide feedback information or understanding of, and to others. Based on these indicators interpersonal communication skills of researchers should be a great concern and the primary strategy of HR competence development of researchers.Komunikasi merupakan salah satu kompetensi yang harus dimiliki oleh peneliti berdasarkan Peraturan Kepala LIPI no 04 tahun 2009 mengenai standar kompetensi peneliti. Kurangnya kemampuan komunikasi interpersonal pada SDM peneliti menjadi dilema tersendiri bagi individu peneliti dan organisasi, karena akan berakibat pada kurang maksimalnya penyebaran informasi akan hasil penelitian ke pada lingkungan penelitian dan sosial. Tipologi kepribadian Jung dengan The Myers-Briggs Type Indicator (MBTI) dapat menggambarkan kemampuan komunikasi interpersonal, menjelaskan indikatornya, dan interpretasi. Pengukuran tipologi kepribadian peneliti menggunakan survey kuesioner MBTI di pusat penelitian X secara purposive random sampling melibatkan sebanyak 42 peneliti meliputi dua kelompok penelitian yaitu Kebijakan dan Indikator IPTEK, dan Manajemen IPTEK. Terdapat dua belas tipologi kepribadian yang seimbang antara kepribadian introvert dan ekstrovert. Gambaran mengenai kompetensi komunikasi interpersonal sebagai bagian konsep diri, terkait penampilan peneliti dalam berkomunikasi yang dapat membantu persepsi interpersonal dari lawan bicaranya. Indikator yang menjelaskan kemampuan kompetensi interpersonal peneliti adalah kemampuan dalam memberikan umpan balik informasi atau pemahaman dari dan ke orang lain. Berdasarkan dari indikator tersebut seharusnya keterampilan komunikasi interpersonal peneliti menjadi perhatian yang penting dan menjadi strategi utama pengembangan kompetensi SDM peneliti.